Assessment of Biogas Potential in Batman and Its Economic Comparison with Alternative Energy Sources - Atılğan, Süleyman Atılgan; Ercan, Umut; Alım, Muzaffer (My University, 2025)
The role of renewable energy sources in ensuring sustainability has become increasingly important as global energy demand continues to rise. However, many of these energy types have limited ability to meet energy demand alone due to their dependence on seasonal or geographic conditions. This challenge highlights the need for leveraging local energy resources, particularly in countries dependent on imported energy sources. Utilizing diverse and local energy sources is critical not only to reduce reliance on imported resources but also to promote energy diversification. From this perspective, biogas can be defined as one of the most accessible energy production technologies. This study conducts Net Present Value (NPV) and Levelized Cost of Electricity (LCOE) analyses for investments in biogas energy, geothermal energy, diesel fuel, fuel oil, and asphalted to help meet the growing energy demand. The research focuses on the economic evaluation of a biogas plant by utilizing organic waste potential in Batman province, aiming to identify the most suitable energy source among regional alternatives. For the biogas energy source, unit costs are calculated as 75.73 $/MWh at a 6% interest rate, 80.65 at 8%, 85.89 at 10%, and 91.41 at 12%. The biogas plant has a payback period of 10 years; after which it becomes profitable. Over its 20-year lifespan, the NPV is projected to reach approximately $1.3 million.
Keywords: Biogas; Biogas potential; Energy economics; Net present value analysis